Pisolithus microcarpus e óleo essencial em três espécies nativas em solo contaminado com cobre - Dellai, Alex (2014)
Mining areas and constantly receiving addition of industrial waste are subject to increased levels of copper in the soil. Copper when in high amounts in the soil can adversely affect vegetation preventing the cultivation of contaminated areas. The aim of this study was to allow the formation of ectomycorrhiza and assess their influence on the development of native tree in soil contaminated with copper. Accordingly, an experiment was established to evaluate the behavior of mimosa, grapia and bracatinga seedlings in copper contaminated soil. Following, another experiment was conducted to evaluate in vitro the influence of eucalyptus essential oil in the establishment of ectomycorrhizal association in bracatinga and grapia seedlings. We evaluated also the influence of eucalyptus essential oil and Pisolithus microcarpus inoculation on growth of bracatinga seedlings in soil contaminated with copper. The results indicate that grápia was less affected by increasing doses of copper applied to the soil and angico that showed lower translocation to leaf area. The bracatinga ectomycorrhizal association formed without the addition of essential oil, however, the presence of oil increased the percentage of ectomycorrhizal colonization, grápia required stimulus eucalyptus essential oil to form ectomycorrhizal association. No effect of inoculating Pisolithus microcarpus was observed in seedling growth bracatinga in soil contaminated with copper, however, we observed a higher altitude at a dose of 180 mg kg - 1 with the application of 40 l L- 1 essential oil eucalyptus . Copper doses from 180 mg kg - 1 inhibit the formation of ectomycorrhiza on seedlings bracatinga .